2008
DOI: 10.1037/0022-3514.95.3.709
|View full text |Cite
|
Sign up to set email alerts
|

Searching for and finding meaning in collective trauma: Results from a national longitudinal study of the 9/11 terrorist attacks.

Abstract: The ability to make sense of events in one’s life has held a central role in theories of adaptation to adversity. However, there are few rigorous studies on the role of meaning in adjustment, and those that have been conducted have focused predominantly on direct personal trauma. The authors examined the predictors and long-term consequences of Americans’ searching for and finding meaning in a widespread cultural upheaval—the terrorist attacks of September 11, 2001—among a national probability sample of U.S. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
221
4
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(255 citation statements)
references
References 93 publications
(200 reference statements)
20
221
4
4
Order By: Relevance
“…Substantial proportions of French people felt shifts in their perceptions of personal safety, thought more about their own mortality, and said they would shift their voting patterns as a consequence. These results expand previous study on 9/11 terrorist attacks (5). Clinicians should be aware that national trauma takes its toll on mental health in various ways including mortality salience, shift in political views and sense of safety.…”
Section: In the Wake Of National Trauma: Psychological Reactions Follsupporting
confidence: 71%
“…Substantial proportions of French people felt shifts in their perceptions of personal safety, thought more about their own mortality, and said they would shift their voting patterns as a consequence. These results expand previous study on 9/11 terrorist attacks (5). Clinicians should be aware that national trauma takes its toll on mental health in various ways including mortality salience, shift in political views and sense of safety.…”
Section: In the Wake Of National Trauma: Psychological Reactions Follsupporting
confidence: 71%
“…Most previous studies addressed the positive impact of personal meaning (i.e., the personal growth and benefit aspects) of coping with threat and trauma (Updegraff et al, 2008). The present studies took a new approach and showed that positive effects of meaning can also be found when meaning is provided on a rather intellectual basis (i.e., providing motives and a rationale for a terrorist attack).…”
Section: Implications and Limitationsmentioning
confidence: 89%
“…This positive coping effect of meaning has been found for a broad variety of extreme adversities, such as coping with the horrifying experiences as a prisoner in a Nazi concentration camp (Frankl, 1963), loss of family members (Davis, Nolen-Hoeksema, & Larson, 1998), loss of a child by the sudden infant death syndrome (McIntosh et al, 1993), severe injuries (Bulman & Wortman, 1977), experiences of violence (Currier, Holland, & Neimeyer, 2006), and terrorism (Updegraff et al, 2008). The positive effects of meaning on coping with adversity have been mainly explained by two processes: (a) meaning provides people with an increased sense of control and security (Heider, 1958;Kelley, 1967), which makes the world more predictable (Roese & Olson, 1996), and (b) meaning attenuates the emotional intensity of unexpected events (Wilson, Centerbar, Kermer, & Gilbert, 2005;Wilson, Gilbert, & Centerbar, 2003; for an overview, see also Updegraff et al, 2008).…”
Section: Meaning and Coping With Terrorist Threatmentioning
confidence: 99%
See 1 more Smart Citation
“…The processed neuropsychological messages elicit a variety of corresponding physiological and emotional reactions that inform both the conscious and unconscious self to adopt different coping skills or defense mechanisms for survival [3]. These patterns of the response style applied by the individuals are likely to affect their ability to access resources from their relational support systems among family and friends, or to recount the sense of identity from communal involvement, or to reconstruct the meaning of their existence and the traumatic disaster itself (Figure 1) [4].…”
Section: Disaster Mental Health the Interconnected Concept Of Psycholmentioning
confidence: 99%